STRATEGI PEMASARAN WAYANG KAMPUNG SEBELAH - Setyabudhi Rahardjo Situmorang (Program Pascasarjana ISI Yogyakarta, 2015)
Wayang Kampung Sebelah (WKS) is one of the phenomenal new genre shadow puppet art show group in today's society and was favored by many people. Their performance in its innovation and creativity of the puppet art show implicates on the marketing methods developed, which results to attracting public attention to the work. The purpose of this study is to determine why WKS was favored among audiences, the marketing methods used and challenges faced in making innovations in a puppet show by WKS. The theory underlying this study refers to the concept of segmentation covering segmentation, targeting and positioning (STP). The study used qualitative research methods. Data analysis was performed based on the theory of marketing strategy with case study approach using a single instrument type with three interviewees. The results showed that the ability of the WKS puppeteer in storytelling and communicating with the audience was a skill difficult to imitate as it was a talent possessed by someone individually thus to attract the audience dissolved in the story told. WKS marketing strategy on the segmentation stage was done using the geographical segmentation by promoting the performance on village societies, which in its development all ages and education eventually become audiences of the group's performances. At the targeting stage, WKS do not choose specifically which consumers is targeted in marketing because the guidelines that are held by WKS, which is that the puppet show should be able to be enjoyed by all people. While on positioning stage, WKS has successfully positioned itself as a puppet group with a unique and hard to imitate style although the idea of the show refers to the style of many traditional puppet show that had long been abandoned. WKS implemented four price levels in the effort to market their work which were as follows: the village attack, subsidized performance attack, public commercial and the professionals commercial. Challenges in creating works comes a lot more from internal factors, which is maintaining the creation spirit of the group, while from external factors there are no significant obstacles but requires a long enough time for WKS to be accepted by the intellectuals (academic society).